Contribuições da análise do comportamento ao processo de inclusão de alunos com diagnóstico de TEA no Rio de Janeiro - Silva, Lilian Fernandes da (2019)
The process of inclusion for a student in the Autism Spectrum Disorder (ASD) cannot be limited to just schools enrollment. Even though we understand this is a recent process, there is a necessity for greater knowledge than what is seen in current legislations. This awareness will contribute to the advancement of inclusive practice, training and performance of professionals involved. The current article initially shows the history of ASD and the inclusiveness of individuals in the Spectrum in schools in Brazil. Secondly, we explore possible contributions of Behavioral Analysis to more effective inclusion. From the important points in the history of inclusive education in Brazil, this study's goal is to understand the reality of Behavioral Analysis and the inclusion of students with ASD in the city of Rio de Janeiro, Brazil